Load profile based empirical model for the lifetime prediction of an automotive PEM fuel cell. (20th April 2017) - Zhang, Xinfeng; Yang, Daijun; Luo, Minghui; Dong, Zuomin
Abstract: The prediction of the lifetime of a PEM fuel cell under a specific electrical load profile is beneficial for automotive applications. An empirical lifetime prediction model coupled with an electrical load profile is presented based on an estimate of the degradation rate of the cell voltage. First, a cause and effect chain-based analysis of the PEM fuel cell's degradation process is presented. Second, a characteristic value is extracted and is treated as a numerical measurement of the effect of load profile on voltage degradation. The characteristic value is defined using both load current and load voltage. Third, an empirical model is proposed, modeling the voltage degradation rate as a linear function of the load profile's characteristic value. Finally, experimental data are used to fit the coefficients and validate the model. Highlights: Cause and effect chain of PEM fuel cell degradation process is presented. A Characteristic value of loading profile is developed to measure its severity. Voltage degradation rate is a linear function of the characteristic value.